Theory-based electronic learning intervention to support appropriate antibiotic prescribing by nurse and pharmacist independent prescribers: an acceptability and feasibility experimental study using mixed methods. Issue 6 (30th June 2020) - Lim, Rosemary; Courtenay, Molly; Deslandes, Rhian; Ferriday, Rebecca; Gillespie, David; Hodson, Karen; Reid, Nicholas; Thomas, Neil; Chater, Angel
Abstract : Objectives: To assess the acceptability and feasibility of using a theory-based electronic learning intervention designed to support appropriate antibiotic prescribing by nurse and pharmacist independent prescribers for patients presenting with common, acute, uncomplicated self-limiting respiratory tract infections (RTIs). Design: Experimental with mixed methods; preintervention and postintervention online surveys and semistructured interviews. Setting: Primary care settings across the UK. Participants: 11 nurse and 4 pharmacist prescribers. Intervention: A theory-based brief interactive animation electronic learning activity comprised a consultation scenario by a prescriber with an adult presenting with a common, acute, uncomplicated self-limiting RTI to support a 'no antibiotic prescribing strategy'. Outcome measures: Recruitment, response and attrition rates were assessed. The overall usefulness of the intervention was assessed by analysing prescribers' self-reported confidence and knowledge in treating patients with RTIs before and after undertaking the intervention, and views on the relevance of the intervention to their work. Acceptability of the intervention was assessed in semistructured interviews. The feasibility of data collection methods was assessed by recording the number of study components completed by prescribers. Results: 15 prescribers (maximum sample size) consented and completed all four stages of the study. Prescribers reported high to very high levels of confidence and knowledge preintervention and postintervention, with slight postintervention increases in communicating with patients and a slight reduction in building rapport. Qualitative findings supported quantitative findings; prescribers were reassured of their own practice which in turn increased their confidence and knowledge in consultations. The information in the intervention was not new to prescribers but was applicable and useful to consolidate learning and enable self-reflection. Completing the e-learning intervention was acceptable to prescribers. Conclusions: It was feasible to conduct the study. The intervention was acceptable and useful to prescribers. Future work will add complex clinical content in the intervention before conducting a full trial.